Community Health Nursing in Slovenia and Croatia – Selected Legal Aspects - Kraljić, Suzana; Kačer, Blanka (Medicine, Law & Society, 2020)
This article is dedicated to community health nursing which today constitutes the indispensable cornerstone of Slovenian and Croatian primary health-care. Authors also stress that community health nursing is recognized of crucial importance for public health and various vulnerable groups (e.g., children, elderly, …) in many other European as well as non-European states. In Chapter 2, the authors represent basic historical milestones in both countries, Slovenia and Croatia, which have common historical roots. In Chapters 3 and 4, the central part of the article, authors analyze the current legal regulation related to community health nursing and thereby give special attention to differences in both national legal regulations. The major difference is given in concessions. Namely in Slovenia, community health nursing can be performed also based on a granted concession, but not in Croatia. In Chapter 5, some legal views on the role of community health nursing in local communities are emphasized (e.g., domestic violence). The last chapter is dedicated to the summarization of the authors’ conclusions, in which they especially stress that the community health nursing in both countries today represents an important key factor for ensuring the constitutional right to health-care.